Association between combat-related traumatic injury and skeletal health: bone mineral density loss is localized and correlates with altered loading in amputees: the Armed Services Trauma Rehabilitation Outcome (ADVANCE) Study - McMenemy,L; Behan,FP; Kaufmann,J; Cain,D; Bennett,AN; Boos,CJ; Fear,NT; Cullinan,P; Bull,AMJ; Phillips,ATM; McGregor,AH (Journal of Bone and Mineral Research, 2023)
The association between combat-related traumatic injury (CRTI) and bone health is uncertain. A disproportionate number of lower limb amputees from the Iraq and Afghanistan conflicts are diagnosed with osteopenia/osteoporosis, increasing lifetime risk of fragility fracture and challenging traditional osteoporosis treatment paradigms. The aim of this study is to test the hypotheses that CRTI results in a systemic reduction in bone mineral density (BMD) and that active traumatic lower limb amputees have localized BMD reduction, which is more prominent with higher level amputations. This is a cross-sectional analysis of the first phase of a cohort study comprising 575 male adult UK military personnel with CRTI (UK-Afghanistan War 2003 to 2014; including 153 lower limb amputees) who were frequency-matched to 562 uninjured men by age, service, rank, regiment, deployment period, and role-in-theatre. BMD was assessed using dual-energy X-ray absorptiometry (DXA) scanning of the hips and lumbar spine. Femoral neck BMD was lower in the CRTI than the uninjured group (T-score -0.08 versus -0.42 p = .000). Subgroup analysis revealed this reduction was significant only at the femoral neck of the amputated limb of amputees (p = 0.000), where the reduction was greater for above knee amputees than below knee amputees (p < 0.001). There were no differences in spine BMD or activity levels between amputees and controls. Changes in bone health in CRTI appear to be mechanically driven rather than systemic and are only evident in those with lower limb amputation. This may arise from altered joint and muscle loading creating a reduced mechanical stimulus to the femur resulting in localized unloading osteopenia. This suggests that interventions to stimulate bone may provide an effective management strategy. © 2023 Crown copyright and The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Soci